Association between phantom limb complex and the level of amputation in lower limb amputee - Bayram Kelle; Erkan Kozanoğlu; Ömer Sunkar Biçer; İsmet Tan (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to evaluate the natural course of phantom limb complex without any treatment after lower limb amputation. Methods: The study design was consisted of a combination of retrospective review and cross-sectional interview. 101 patients with lower limb amputation were included into the study. Patients were divided into three groups according to the amputation level: i) from hip disarticulation to knee disarticulation (including knee disarticulation) (25 patients, mean age: 55.9, 19 males, 6 females) ii) transtibial amputation (below knee to ankle including ankle disarticulation) (41 patients, mean age: 58.6, 33 males, 8 females) iii) below ankle to toe amputation (35 patients, mean age: 58.7, 26 males, 9 females). The patients were evaluated on both early postoperative period (EPP) and sixth months after the surgery (ASM). The data related amputation including amputation date, level, cause, stump pain (SP), phantom limb pain (PLP), components of PLP, phantom sensation (PS) were recorded based on the information obtained from patients' and hospital files. Results: Statistically significant differences were found for pain intensity (VAS) between groups for SP and PLP at EPP (p < 0.001, p = 0.036; respectively). The mean VAS score in Group I for SP and PLP was higher than other groups. This differences for SP and PLP did not continue at ASM assessment (p = 0.242, p = 0.580; respectively). Conclusion: VAS scores for SP in above knee amputations and VAS scores for PLP in above knee amputations and below ankle amputations were higher at EPP. But these high scores had disappeared over time. Management strategies have to be considered particularly in the early postoperative period in patients who had undergone above knee amputation. Level of Evidence: Level III Prognostic study. Keywords: Level of amputation, Lower limb amputation, Phantom limb pain, Phantom sensation, Stump pain